Konservasi In Vitro Kantong Semar (Nepenthes rafflesiana Jack.) dengan Metode Slow Growth - Previaningrum, Hanum; Qadir, Abdul; Isnaini, Yupi (Jurnal Jejaring Matematika dan Sains, 2021)
Nepenthes rafflesiana Jack. is one of a unique plant because there is the pitcher on the tips of the leaves to trap insects. This uniqueness makes N. rafflesiana mostly taken from its natural habitat for sale. Big Explored from nature caused extinction and ecosystem habitats damaged. Efforts to prevent extinction through ex situ conservation by in vitro culture of N. rafflesiana with slow growth method. This study aims were to determine the effect of paclobutrazol on the growth of N. rafflesiana and to obtain the most suitable concentration of paclobutrazole for in vitro conservation of N. rafflesiana. The research was conducted at the Tissue Culture Laboratory of the Research Center for Plant Conservation and Botanical Gardens from January to April 2020. The experiment was carried out in a Completely Randomized Group Design with a single factor, namely the concentration of paclobutrazol: 0, 1, 3 and 5 ppm. The results showed that the best concentration of paclobutrazol for in vitro conservation of N. rafflesiana was 5 ppm which could inhibit the growth of stem height and number of leaves and could maintain the green color of the leaves.